Pengaruh Kompensasi dan Disiplin Kerja Terhadap Kinerja Karyawan PT Nouf Teknik Nusantara - Mega Rossalia Nopier Aristia; Joko Ariawan (Pusat Riset dan Inovasi Nasional, 2025)
PT Nouf Teknik Nusantara is a company operating in the marine and electrical sector. PT Nouf Teknik Nusantara makes a full contribution to the Indonesian shipping industry. It cannot be denied that competition is currently at the highest level in the trade sector, especially in the Marine and Electrical trade sector, there are many competitors who are superior in providing services and in procuring goods, according to consumer needs. This research aims to analyze and determine the effect of compensation and work discipline on employee performance at PT Nouf Teknik Nusantara. This type of research uses a questionnaire distributed to employees of PT Nouf Teknik Nusantara. The data collected from the questionnaire is tabulated and then processed. To carry out data processing, researchers used SPSS 27 software. The results of this research show that compensation influences employee performance at PT Nouf Teknik Nusantara, work discipline influences employee performance at PT Nouf Teknik Nusantara, compensation and work discipline simultaneously influence employee performance at PT Nouf Teknik Nusantara.